POLA DAN KETERSEDIAN SARANA DAN PRASARANA PERMUKIMAN DESA PONDOK KECAMATAN BUKIT KERMAN KABUPATEN KERINCI - ahmad rafan rafan; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This research aims to determine the pattern of community settlements in the pondok village of Bukit Kerman sub-district Kerinci regency, knowing the conditions of the facilities and infrastructure in the pondok village, Bukit Kerma DistrictKerinci Regency, knowing the factors of the community living in the Pondok Village, Bukit Kerman District, Kerinci District. This type of research is descriptive quantitative which describes the research area with primary data and secondary data. The field survey method is carried out to observe, record and measure the object of research. The data collection technique was done by using purposive sampling technique, namely by determining specific characteristics in accordance with the research objectives Based on the research results, it can be seen that: 1) The settlement pattern in Pondok Village, Bukit Kerman DistrictKerinci Regency is a grouping pattern, generally the settlements follow the road and cluster in certain places. The conditions of housing in Pondok Village are generally semi-permanent, single houses and included in simple houses, with adequate housing facilities. 2) Environmental infrastructure in Pondok Village is quite adequate, such as roads, waterways, and electricity networks. Environmental facilities in Pondok village are adequate, such as educational facilities for elementary schools, junior high schools, health services, shopping such as food stalls, religious services. 3) The main factor for the community residing in Pondok village is that they have lived in the area from generation to generation, and the ownership status of the runah generally belongs to themselves.